2010
DOI: 10.1038/jhg.2010.62
|View full text |Cite
|
Sign up to set email alerts
|

MDM2 SNP309 and p53 Arg72Pro in cutaneous melanoma: association between SNP309 GG genotype and tumor Breslow thickness

Abstract: A functional single nucleotide polymorphism (SNP) 309 T/G within mouse double minute 2 (MDM2) gene has been linked to onset and outcome of disease in tumors. Two published studies have shown discordant results regarding the effect of this SNP on age at diagnosis of cutaneous melanoma (CM) in Caucasian female populations. Here, we examined the age at diagnosis and clinical associations of CM with SNP309 and the related polymorphism, p53 Arg72Pro, in an Italian population (249 CM patients and 291 cancer-free con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 33 publications
(71 reference statements)
2
14
0
Order By: Relevance
“…Collectively, the studies by Nan et al (2009), Capasso et al (2010, and ours agree in that the MDM2 SNP309 G does not appear to be a risk factor for developing melanoma at a young age. A very recent report unveils a second MDM2 promoter SNP in position 285 (SNP285G4C), which forms a distinct haplotype with SNP309 (SNP285C/SNP309G) (Knappskog et al, 2011).…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…Collectively, the studies by Nan et al (2009), Capasso et al (2010, and ours agree in that the MDM2 SNP309 G does not appear to be a risk factor for developing melanoma at a young age. A very recent report unveils a second MDM2 promoter SNP in position 285 (SNP285G4C), which forms a distinct haplotype with SNP309 (SNP285C/SNP309G) (Knappskog et al, 2011).…”
Section: Discussionsupporting
confidence: 59%
“…However, when we stratified the groups into gender and decades of age at diagnosis, we found an increased frequency of the GG genotype among women diagnosed at an older age, which does not support the hypothesis of an active estrogen signaling via the SNP309 GG genotype. Another study conducted in 249 cases and 291 controls found that women having the SNP309 GG genotype were diagnosed at an older age, although the association did not reach statistical significance (Capasso et al, 2010). The same authors found a positive association between the GG genotype and tumor thickness (Capasso et al, 2010).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Additionally, it was shown that a SNP in the MDM2 gene, the SNP309 (T>G variation) was linked to the tumour onset and outcome. However, discordant results were reported on the effect of this SNP on age at diagnosis of cutaneous melanoma in Caucasian female population and no associations were found among SNP309, melanoma risk, age at diagnosis and presence of metastasis in the Italian population, although SNP309 was significantly associated with tumour Breslow thickness (Capasso et al, 2010). It was proposed that the Vitamin D Receptor (VDR) gene might play a role in melanoma development as well, since its interaction with the calcitriol ligand results in antiproliferative and pro-differentiation signals on melanocytes.…”
Section: Other Genesmentioning
confidence: 68%